Reconstruction of Integrative Methods in Merdeka Curriculum for Islamic Education Subjects - Astuti, Mardiah; Ismail, Fajri (Al-Hayat: Journal of Islamic Education, 2025)
Islamic Education learning is required to be able to adapt to the values of independence, critical thinking, and contextual as the principles of the Merdeka Curriculum. This study aims to explore and reconstruct the integrative learning method within the framework of the Merdeka Curriculum in the subject of Islamic Education. This type of research is qualitative with a descriptive approach. Data collection was carried out through interviews, observations, and documentation. Furthermore, the data was analyzed by data reduction, data presentation, and conclusions. The results of the study show that the integrative method in Islamic Education learning in the Merdeka Curriculum provides a comprehensive approach that combines holistic methods, technology integration, use of reflective journals, project-based learning, guest speakers/field visits, and community service-based learning. This method is able to improve the understanding of Islamic teachings, character development, and social involvement of students, in line with the overall goals of Islamic education. This study is limited to certain levels of education and has not tested the effectiveness of the method quantitatively. Further research is recommended using a quantitative approach or experiments at different levels to assess the impact of the integrative method in a more measurable manner.